Partisipasi Masyarakat Dalam Pengembangan Desa Wisata di Kelurahan Sarangan Kabupaten Magetan - Irham Abidurrahman; Mohammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2018)
The problems local government has been facing in the development of Sarangan Tourism Village was backed by the existence of many weakness, misunderstanding, and conflicts as it seen through the low citizen participation. This includes a minimum sense of responsibility towards the development of existing tourism sites for instance. All because the respective local community already get used with the system of development given from the higher lawmakers (top down process) so that people perceive such tendency to become passive and moreover only wait for initiatives from external stakeholders.The main purpose of this study is to examine forms and level of community participation and to determine all possible factors which has been influencing community participation activity in Sarangan Tourism Village development program. This research uses quantitative descriptive analysis by deploying questionnaire as information digging tool supported by qualitative data in which will be extracted from interview process.Based on the result of the research, it is found that community participation in the research area is related to the participatory forms of social funding, collective physical activity, self-property donation, and softskill training session, in which majority of people dominantly participate in the social funding forms, followed by self-property donation, collective physical activity, and softskill training session as it’s counted in order. Overall the level of community participation in Sarangan Tourism Village is at the second level of Sherry Arnstein’s eight participation degrees, specifically mentioned as therapy level which also belongs to non-participation category. In addition, there is a strong correlations between internal factors of income levels, external factors of community leaders, local governments, and village officials on the level of community participation in all development stages that includes the stage of planning, implementation, and evaluation.